Rotavirus Binding to Cell Surface Receptors Directly Recruiting α2 Integrin. Issue 12 (8th December 2021) - Yang, Jinsung; Park, Jeongsoo; Koehler, Melanie; Simpson, Joshua; Luque, Daniel; Rodríguez, Javier M.; Alsteens, David
Abstract : Virus–Receptor Interactions In article number 2100077, David Alsteens and co‐workers report that Rotavirus binding and early entry is mediated by an integrin on the cell surface. The binding is assessed by Atomic Force Microscopy, while recruitment of internalization machinery is monitored by confocal imaging. The interaction between rotavirus VP8* and CHO cell α2 β1 integrins induces clathrin pit formation, contributing to successful viral infection.